2014
DOI: 10.6017/ijahe.v1i1.5648
|View full text |Cite
|
Sign up to set email alerts
|

The Regionalisation, Internationalisation, and Globalisation of African Higher Education

Abstract: The landscape of international higher education has been changing since the turn of the 21st century. The globalisation of our societies and economies implies a changing role of the higher education institutions. Accompanying the challenges associated with development, especially in developing countries, are initiatives championing regionalisation as a locus of development. This article positions the debate on the relationships among globalisation, regionalisation, and internationalisation in the context of Af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
1
19
0
Order By: Relevance
“…The student mobility aspect of internationalisation (especially for a context like Zimbabwe) thus becomes one of its most important features, similar to what exists in the global North, which is also heavily about student mobility. However, Sehoole and De Wit (2014) There is an awareness amongst many Zimbabwean academics that the current interest in internationalisation is also about economic benefits. In a pragmatic vein, one VC noted that the current interest in internationalisation had little to do with the wider benefits, though he believed in them.…”
Section: Student Mobilitymentioning
confidence: 99%
“…The student mobility aspect of internationalisation (especially for a context like Zimbabwe) thus becomes one of its most important features, similar to what exists in the global North, which is also heavily about student mobility. However, Sehoole and De Wit (2014) There is an awareness amongst many Zimbabwean academics that the current interest in internationalisation is also about economic benefits. In a pragmatic vein, one VC noted that the current interest in internationalisation had little to do with the wider benefits, though he believed in them.…”
Section: Student Mobilitymentioning
confidence: 99%
“…We recognize that many of the definitions for internationalization come from a Westernized or a Global North perspective. Global South scholars (Jooste & Heleta, 2017; Sehoole & De Wit, 2014) nuance the term internationalization and warn against the tacit hegemony implied within the term. If left unquestioned, internationalization can become a coded word that masks and further reproduces the inequities of access and opportunities.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Studies on the internationalisation of the student community in Africa include Sehoole and De Wit's (2014) research that observed that the internationalisation of higher education on the continent has followed the same pattern as that in other parts of the world, especially Europe and North America. They added that this has meant that African universities and students have reaped few benefits from the process.…”
Section: Introductionmentioning
confidence: 99%